1997
DOI: 10.1115/1.2841008
|View full text |Cite
|
Sign up to set email alerts
|

Grid Orthogonality Effects on Predicted Turbine Midspan Heat Transfer and Performance

Abstract: The effect of five different C type grid geometries on the predicted heat transfer and aerodynamic performance of a turbine stator is examined. Predictions were obtained using two flow analysis codes. One was a finite difference analysis, and the other was a finite volume analysis. Differences among the grids in terms of heat transfer and overall performance were small. The most significant difference among the five grids occurred in the prediction of pitchwise variation in total pressure. There was consistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…Thus, this model is likely to be invalid in a number of turbomachinery applications but for turbine blades, the boundary layers generally experience a favorable pressure gradient whereby this model is more likely to be valid. It has been used satisfactorily by Boyle and Giel (1992), Ameri and Amone (1994a, b), and Boyle and Ameri (1994) for heat transfer calculations on turbine blades without film cooling, and by Hall et al (1994), and Garg and Gaugler (1994) with film cooling. In fact, Ameri and Amone (1994b) compared the Baldwin-Lomax model and Coakley's q-co model against experimental data of Graziani et al (1980), and found that the algebraic model was able to produce many of the flow features better than the twoequation model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this model is likely to be invalid in a number of turbomachinery applications but for turbine blades, the boundary layers generally experience a favorable pressure gradient whereby this model is more likely to be valid. It has been used satisfactorily by Boyle and Giel (1992), Ameri and Amone (1994a, b), and Boyle and Ameri (1994) for heat transfer calculations on turbine blades without film cooling, and by Hall et al (1994), and Garg and Gaugler (1994) with film cooling. In fact, Ameri and Amone (1994b) compared the Baldwin-Lomax model and Coakley's q-co model against experimental data of Graziani et al (1980), and found that the algebraic model was able to produce many of the flow features better than the twoequation model.…”
Section: Discussionmentioning
confidence: 99%
“…2). Normal to the blade surface is the dense viscous grid, with y' < 1 for the first point off the blade surface, following Boyle and Giel (1992). Computations were run on the 8-processor Cray Y-MP supercomputer at the NASA Lewis Research Center, and on the 16-processor C-90 supercomputer at NASA Ames Research Center.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are thought to be due to some truncation errors in the specification of geometry points, as other authors like Gehrer and Jericha [21] Boyle and Ameri [22] have reported. In order to solve such problem; a redesign of the geometry was performed while keeping the same pressure distribution and global geometry constraints.…”
Section: Mu 2 S 2 T Validationmentioning
confidence: 81%
“…Using the Baldwin-Lomax turbulent model, Boyle and Ameri 9) observed a discrepancy between the numerical and experimental total pressure values at the 0.42 axial chord behind the blade. They attributed this discrepancy to the conjecture that the amount of diffusion in the wake predicated by the turbulent model is too small.…”
Section: Wakementioning
confidence: 99%